AEgIS at ELENA: outlook for physics with a pulsed cold antihydrogen beam. (19th February 2018) - Doser, M.; Aghion, S.; Amsler, C.; Bonomi, G.; Brusa, R. S.; Caccia, M.; Caravita, R.; Castelli, F.; Cerchiari, G.; Comparat, D.; Consolati, G.; Demetrio, A.; et al.
Abstract : The efficient production of cold antihydrogen atoms in particle traps at CERN's Antiproton Decelerator has opened up the possibility of performing direct measurements of the Earth's gravitational acceleration on purely antimatter bodies. The goal of the AEgIS collaboration is to measure the value of g for antimatter using a pulsed source of cold antihydrogen and a Moiré deflectometer/Talbot–Lau interferometer. The same antihydrogen beam is also very well suited to measuring precisely the ground-state hyperfine splitting of the anti-atom. The antihydrogen formation mechanism chosen by AEgIS is resonant charge exchange between cold antiprotons and Rydberg positronium. A series of technical developments regarding positrons and positronium (Ps formation in a dedicated room-temperature target, spectroscopy of the n =1–3 and n =3–15 transitions in Ps, Ps formation in a target at 10 K inside the 1 T magnetic field of the experiment) as well as antiprotons (high-efficiency trapping of, radial compression to sub-millimetre radii of mixed plasmas in 1 T field, high-efficiency transfer of to the antihydrogen production trap using an in-flight launch and recapture procedure) were successfully implemented. Two further critical steps that are germane mainly to charge exchange formation of antihydrogen—cooling of antiprotons and formation of a beam of antihydrogen—are being addressed in parallel. The coming of ELENA will allow, in the very near future, the number of trappable antiprotons to be increased by more than a factor of 50. For the antihydrogen production scheme chosen by AEgIS, this will be reflected in a corresponding increase of produced antihydrogen atoms, leading to a significant reduction of measurement times and providing a path towards high-precision measurements. This article is part of the Theo Murphy meeting issue 'Antiproton physics in the ELENA era'.